2010
DOI: 10.1167/iovs.09-4310
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Injections of Neurotrophic Factors Secreting Mesenchymal Stem Cells Are Neuroprotective in Rat Eyes following Optic Nerve Transection

Abstract: Bone marrow-derived MSCs can deliver NTFs by intravitreal injection and can be neuroprotective after ONT. This approach might be further studied to deliver NTFs by autotransplantation in glaucomatous eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
1
11

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(84 citation statements)
references
References 40 publications
0
72
1
11
Order By: Relevance
“…5 It has been shown that various neurotrophic factors released by MSCs may be involved in the repair of degenerative retina, including CNTF, BDNF, NT-3, GDNF, bFGF, HGF-a, and PEDF. 5,6,11,[32][33][34][35] Furthermore, we speculated that MSCs may affect the expression and release of cytokine by retinal resident cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 It has been shown that various neurotrophic factors released by MSCs may be involved in the repair of degenerative retina, including CNTF, BDNF, NT-3, GDNF, bFGF, HGF-a, and PEDF. 5,6,11,[32][33][34][35] Furthermore, we speculated that MSCs may affect the expression and release of cytokine by retinal resident cells.…”
Section: Discussionmentioning
confidence: 99%
“…Engineering of MSCs to produce neurotrophic growth factors has been explored as an attractive mode of long-term delivery of neuroprotective substances to the retina affected by disease. 26,35,45,46 Intravenous and intratracheal delivery of MSCs expressing CX3CL1 in mice bearing multiple lung tumors could induce strong anti-tumor effects. 47,48 We demonstrated that genetically modified MSCs can deliver CX3CL1 to the retina.…”
Section: Discussionmentioning
confidence: 99%
“…To understand the pathophysiology of a compressed optic nerve and to develop novel therapies for sellar area tumors, it is important to have relevant disease models of optic nerve compression in which new treatment strategies can be assessed before clinical trials are initiated. Most optic nerve compression models presently used are based on direct, acute injury of optic nerves by transection or crushing, which produces a different pathogenesis and pathophysiology than the chronic compression of optic nerves by tumors [23,24,25,26]. In this study, we first created cat models of optic nerve compression by compressing chiasm with balloons, producing compression that has similar electrophysiological and pathological characteristics to compression from tumors.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] Although trophic factor secretion is undoubtedly important in some contexts, other factors may be equally or more critical in other situations, and should be explored. For instance, some types of stem cells possess an array of immunomodulatory properties that protect neurons during inflammatory neurodegeneration;…”
Section: Broadening the Focus On Mechanisms Of Actionmentioning
confidence: 99%